2022
DOI: 10.1039/d2tb00614f
|View full text |Cite
|
Sign up to set email alerts
|

Latest on biomaterial-based therapies for topical treatment of psoriasis

Abstract: Psoriasis is an autoimmune inflammatory disease which is fundamentally different from dermatitis. Its treatments include topical medications and systematic drugs depending on different stages of the disease. However, these commonly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 129 publications
0
8
0
Order By: Relevance
“…Psoriasis is an inflammatory skin disease mainly mediated by immunity and it affects millions of people around the world [1] , [2] . It is reported that topical therapy, phototherapy, and immunotherapy have been used for the treatment [3] , [4] , [5] . Topical therapy mainly utilizes drugs such as retinoids, vitamin D derivatives to treat psoriasis [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is an inflammatory skin disease mainly mediated by immunity and it affects millions of people around the world [1] , [2] . It is reported that topical therapy, phototherapy, and immunotherapy have been used for the treatment [3] , [4] , [5] . Topical therapy mainly utilizes drugs such as retinoids, vitamin D derivatives to treat psoriasis [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Transdermal drug delivery is an effective route for the treatment of skin diseases, because it allows direct targeting of lesions on the skin and reduces the side effects associated with systemic drug delivery (90)(91)(92)(93). However, the skin barrierstratum corneum could greatly impair the bioavailability of transdermal drug delivery.…”
Section: Microneedles-mediated Drug Delivery For the Treatment Of Pso...mentioning
confidence: 99%
“…unique advantages, microneedles have been widely used as effective transdermal drug delivery tools for the treatment of skin diseases including psoriasis (90,91,94). Du et al developed a microneedle patch made with hyaluronic acid (HA) and encapsulated MTX into the patch, which could effectively penetrate the IMQ-induced mouse epidermis and impair psoriasis-like skin inflammation in mice (95).…”
Section: Microneedles-mediated Drug Delivery For the Treatment Of Pso...mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with those of healthy skin, psoriatic lesions are thicker and have greater transepidermal water loss, which limit effective transdermal delivery. 20 Another challenge for delivery is the hydrophobic nature of calcipotriol and its low permeation through the stratum corneum . 21 Therefore, developing a new drug delivery system with fewer side effects to improve patient adherence to therapies is highly desirable.…”
Section: Introductionmentioning
confidence: 99%